Handbook of Translation Studies : Volume 4 - Gambier, Yves, 1949-; Doorslaer, Luc van, 1964- (Handbook of Translation Studies., 2013)
As a meaningful manifestation of how institutionalized the discipline has become, the new 'Handbook of translation studies' is most welcome. It joins the other signs of maturation such as Summer Schools, the development of academic curricula, historical surveys, journals, book series, textbooks, terminologies, bibliographies and encyclopedias. The HTS aims at disseminating knowledge about translation and interpreting and providing easy access to a large range of topics, traditions, and methods to a relatively broad audience: not only students who often adamantly prefer such user-friendliness, researchers and lecturers in Translation Studies, Translation & Interpreting professionals; but also scholars and experts from other disciplines (among which linguistics, sociology, history, psychology).